Editorial. (2016) - Paul, Lijo; Baby, Rajesh
Abstract: The editorial introduces the first Global Colloquium on Recent Advancements and Effectual Researches in Engineering, Science and Technology – RAEREST 2016, held from April 22 nd to 23 th, 2016 at St. Joseph's College of Engineering and Technology, Palai, Kerala, India. This editorial aims at highlighting the host institute and the major motivation behind organizing the global colloquium. Further, it introduces the plenary and keynote speakers and elaborates scope as well as topics discussed in the colloquium.